Smart water leak detection using wireless sensor networks - Rahman, Mahfujur; Islam, Md Raishul; Islam, S M Atikul; Shajal, Md. Afjal Hossan (Review of Computer Engineering Research, 2025)
This study explores the use of remote sensor systems to detect leaks in underground water pipelines, aiming to tackle the problem of water loss in distribution networks. Identifying and preventing such leaks is essential for the sustainable management of natural water resources. To address this challenge and improve leak detection, the authors designed a remote system that utilizes flexible wireless sensors to identify leaks while minimizing energy consumption. This system also evaluates the time and cost efficiency of smart water leakage detection (SWLD) in pipelines, monitors water levels in storage tanks, and automatically activates controls when water levels drop below a set threshold. The proposed approach is built around two main components. The first utilizes GSM (Global System for Mobile Communications) technology to send SMS alerts to the owner. Core elements of this system include sensors, a GSM module, an Arduino board, and a switch for device control. The second component features an Android-based application that allows for remote management of the system. By enabling early leak detection, the system aims to lower the costs and time involved in pipeline maintenance, enhance operational efficiency, and reduce long-term repair efforts.